Increased attention to the eye region when playing background music in Alzheimer's disease: a remotely-delivered webcam eye-tracking feasibility study - Anne-Marie Greenaway; Faustina Hwang; Slawomir Nasuto; Aileen K. Ho (Cogent Gerontology)
Music modulates dwell-times on discriminating facial features (e.g. eyes) and rumination levels modulate visual attention/responses to music. As these factors are understudied in dementia, particularly in non-care settings, home-based music research with webcam-based eye tracking (WBET) was explored. Participants completed online self-report mood/rumination measures and a cognitive status interview. In silence and then with background music, participants fixated on a cross, naturally viewed emotional-neutral facial pairings, and then fixated on a dot. Percentage dwell-time on emotional faces, and the top-half versus bottom-half of these images was examined and changes were registered by the eye tracker during the music condition. WBET use was feasible (i.e. full datasets were collected for both conditions) for 39% of the participants. Data could not be collected from 33% of the participants due to initial calibration failures attributed to head movement and/or blinking, and face detection and internet connection issues. All other issues could be resolved remotely with assistance. In conclusion, WBET use in music-based research is feasible and provides access to eye-tracking studies for some individuals. The large amount of data/participant loss should be considered in sample size calculations. Practical recommendations, preliminary data, and hypotheses based on these data are provided for future research.